Effects of Intercalation and Deintercalation in Layered Materials: From Topological Insulators to Battery Cathodes - (:unkn) unknown (My University, 2020)
Topological insulators are quantum materials which have insulating bulk and conducting surface. The surface states in these materials is protected by time reversal symmetry and spin-orbit coupling. The fascinating quantum properties of these materials could lead to high speed electronics and quantum computing. To explore the transport properties of these systems, I synthesized single crystals of SnTe and Sb2Se3 which are potential topological insulators. SnTe is a topological crystalline insulator in which topological surface states are protected by time reversal symmetry and crystal symmetry, in particular mirror symmetry. My Shubnikov-de Haas (SdH) oscillation study on the (001) surface of SnTe under low temperatures up to 0.35 K and at high magnetic fields up to 18T indicates the presence of cylindrical Fermi surface and topological states on (001) surface of SnTe. My results confirm the theoretical prediction of topological states on {100} surface of SnTe by previous authors. In addition, I also studied the transport properties of antimony selenide (Sb2Se3), a band insulator with a 1 eV bandgap under ambient conditions which is metallic above 3 GPa, and superconducting above 10 GPa. Our single crystals are orthorhombic, unlike rhombohedral Bi2Se3 and Sb2Te3. Following up on our previous collaborative studies of Raman spectroscopy and first-principles density functional theory (DFT), which revealed an electronic topological transition (ETT) with pressure, we performed non-contact conductivity measurements using a tunnel diode oscillator (TDO) circuit under high pressure in a diamond anvil cell. A Fermi Surface (FS) is found to appear at 6.4 GPa indicating a possible insulator to metallic transition. We also find evidence for a Berry phase (β) of value π indicating possible non-trivial topologies. In addition, I also synthesized high energy density layered sodium-ion cathode materials and studied the effects of intercalation and de-intercalation of sodium ions on crystal structure of pristine material. P2-type Na0.67Mn0.65Fe0.35O2 (NMFO) displays high reversible capacity (185 mAhg-1) and undergoes structural transitions between P63/mmc, P63 (OP4) and orthorhombic Cmcm space groups during charge-discharge cycling between 1.5 and 4.3 V. My study shows that the substitution of Jahn-Teller active Fe with nickel and cobalt suppresses structural transition in P2-type Na0.67Mn0.625Fe0.25Ni0.125O2 (NMFNO) and P2-type Na0.67Mn0.625Fe0.25Co0.125O2 (NMFCO). The discharge capacity and specific energy of NMFNO and NMFCO are higher than that of NMFO up to 100 cycles in the 1.5–4.0 V range, and to at least 200 cycles for 2.0–4.0 V range. I further studied morphology changes of cycled cathodes and performed impedance measurements. I observed the formation of cracks and SEI layer on the surface of the cycled cathodes. The total impedance of NMFNO and NMFCO between 1000 kHz and 0.1 Hz is significantly lower than NMFO after 200 cycles.